Daya Lenting (Resilience) Pada Perempuan Korban Perkosaan - Iyulen Pebry Zuanny; Marty Mawarpury; Maya Khairani (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
This case study research aimed to see the resilience of women victims of rape. Four respondents are women rape victims who lived in Aceh and were selected using purposeful sampling and snowball sampling methods. Snowball sampling based on certain parties who know the source and location of the repondents. Data were collected using interviews and observation methods. Data analysis was performed with a theme per-subject analysis. Data were analyzed by interpreting and summing up the results of the interview each respondent. Interview guide was developed based on the aspects of resilience by Bonanno (2004). The results showed that resilience of four subjects are different.Keywords: Resilience, Rape, Women Victims of rape